2007
DOI: 10.1111/j.1708-8305.2007.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity Study of Abbreviated Rabies Preexposure Vaccination Schedules: Table 1

Abstract: It might be possible to develop a 1-week and even one clinic visit preexposure vaccine schedule that would provide at least 1 year of immune memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 6 publications
0
33
0
2
Order By: Relevance
“…In one of the study arms, Khawplod and coworkers administered two ID doses at two sites on a single visit as primary vaccination, using PCECV or PVRV. Upon two ID booster doses (Day 0 and 3) one year later, all subjects elicited anamnestic immune responses and adequate RVNA concentrations [19]. …”
Section: Discussionmentioning
confidence: 99%
“…In one of the study arms, Khawplod and coworkers administered two ID doses at two sites on a single visit as primary vaccination, using PCECV or PVRV. Upon two ID booster doses (Day 0 and 3) one year later, all subjects elicited anamnestic immune responses and adequate RVNA concentrations [19]. …”
Section: Discussionmentioning
confidence: 99%
“…There were 11 citations identified that reported immunogenicity data following ID PVRV for PrEP [16,[20][21][22][23][24][25][26][27][28][29]; of these, 6 were undertaken in Thailand [20,23,25,[28][29][30]. The other studies were undertaken in Vietnam [24,27] (both these Vietnamese studies reported data on the same cohort of children), Brazil [22], and The Netherlands [16,21].…”
Section: Immunogenicity Of Prep Regimensmentioning
confidence: 99%
“…Seroconversion rates from day 14 to 56 after the first vaccination and at 1 year across the studies identified were 90-100% and 20-96%, respectively [16,[21][22][23]25,[27][28][29]. The RVNA GMTs reported across the studies irrespective of PrEP regimen (n = 926), including following booster vaccination after one year, are summarized in Figure 2 [16,[20][21][22][23][24][25][26][27][28][29].…”
Section: Immunogenicity Up To 1 Yearmentioning
confidence: 99%
“…Previous studies utilizing the PCEC-K intradermal regimen reported that, 6 months after immunization, approximately half the subjects had reduced NA titers below 0.5 IU/ml and responded well to booster vaccination [5]. Khawplod et al [11] have also shown that an intradermal booster dose achieved significant NA titers. It is strongly suggested by our data that a 0.1-ml booster inoculation of PCEC-K will produce protective titers, making the intradermal protocol a putative candidate for booster vaccination.…”
Section: Discussionmentioning
confidence: 96%